Automatic Radio Compass is a Method of Reducing the Noise and Interference of the Radio Receiver - Polatbayevna, Embergenova Nilufar; Gulmirzoevna, Bozorboyeva Salomat; Murodboy o'g'li, Qoshmanov Ergash (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, we describe the automatic radio compass and its functions, its prevention of radio receiver noise and interference from outside. Radio receiver (abbreviated name - receiver, oral - radio) - a device connected to an antenna, used for radio reception, that is, for separating signals from radio waves.